2021
DOI: 10.3390/microorganisms9051063
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Properties of Probiotic Candidate Strains Isolated during Fermentation of Agave (Agave angustifolia Haw)

Abstract: Agave species are a source of diverse products for human use, such as food, fiber, and beverages, which include mezcal, a distilled beverage produced by spontaneous fermentation. Agave is an excellent source of high amounts of sugars, minerals, and phenolic compounds, which favor the growth of lactic acid bacteria (LAB) and yeast communities. In this work, 20 promising LAB strains with probiotic characteristics were isolated from the agave fermentation stage in mezcal production. The strains belonged to Lactob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
(70 reference statements)
1
9
0
Order By: Relevance
“…Treatment with L.brevis , L.pentosus , and L.curvatus reduces Salmonella -induced-IL-1β, IL-6, IL-8 mRNA levels and the p-IκB-α level, and increases cytokine IL-10 production and zonula occludens-1 (ZO-1)-mediated tight-junction integrity in HT-29 human IEC via the inhibition of the NF-κB pathway [ 108 ]. L.plantarum LM17 and L.rhamnosus LM07 strains exert anti-inflammatory activity in TNF-α-induced HT-29 human IEC by reducing cytokine IL-8 production [ 109 ]. L.kefiri strain CIDCA 8348 reduces TNF-α, IFN-γ, cytokines IL-6, IL-13 production, and increases cytokine IL-10 production and CD4 + FOXP3 + T cell expression in the inflamed mucosa of IBD patients [ 110 ].…”
Section: Gut Microbiota-derived Scfas As Therapeutic Potential Agents...mentioning
confidence: 99%
“…Treatment with L.brevis , L.pentosus , and L.curvatus reduces Salmonella -induced-IL-1β, IL-6, IL-8 mRNA levels and the p-IκB-α level, and increases cytokine IL-10 production and zonula occludens-1 (ZO-1)-mediated tight-junction integrity in HT-29 human IEC via the inhibition of the NF-κB pathway [ 108 ]. L.plantarum LM17 and L.rhamnosus LM07 strains exert anti-inflammatory activity in TNF-α-induced HT-29 human IEC by reducing cytokine IL-8 production [ 109 ]. L.kefiri strain CIDCA 8348 reduces TNF-α, IFN-γ, cytokines IL-6, IL-13 production, and increases cytokine IL-10 production and CD4 + FOXP3 + T cell expression in the inflamed mucosa of IBD patients [ 110 ].…”
Section: Gut Microbiota-derived Scfas As Therapeutic Potential Agents...mentioning
confidence: 99%
“…Saponins obtained from Agave americana were also studied as an additive in animal feeding [54]. Several studies reported that these LAB strains participated during agave fermentation [17,18,55,56]. For this reason, agave is both a prebiotic and probiotic promising source for the development of novel functional food products.…”
Section: Agavementioning
confidence: 99%
“…The vast research findings in these food matrices have demonstrated functional and nutritional attributes due to their fiber-like type 2 RS, agavins [13]; fiber mucilage [14], water extractable polysaccharides [15], and antioxidants [16,17]. Furthermore, their microorganism content improves the shelf-life of the product, its sensorial characteristics, and probiotic properties [18,19]. The isolation, characterization and association of the prebiotics and probiotics from the food matrices has become a suitable alternative for the development of new products [19].…”
Section: Introductionmentioning
confidence: 99%
“…To determine the antioxidant activity of probiotics, this can be performed directly in intact cells and cell extracts of bacterial strains by 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging ability or by using in vitro cellular models [ 67 ]. For example, coincubation of Lactobacillus species in HT-29 cells in the presence of 2 mM H 2 O 2 , and subsequent measurement of thiobarbituric-acid-reactive substances, total antioxidant status (TAS), superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT), and lipid peroxidation products [ 68 ]. Another example was proposed by Wang et al [ 69 ], using the supernatants of B. longum CCFM752, L. plantarum CCFM1149, or L. plantarum CCFM10 in coincubation with A7R5 cells (a rat cell line that has been used to study the effect of angiotensin II on vascular oxidative stress).…”
Section: Target Screening To Select Bacterial Strains With Probiotic ...mentioning
confidence: 99%